Rethinking The Body in Pain. Issue 4 (December 2016) - McIntyre, Michael
Abstract This article calls into question two core suppositions of "The Body in Pain": that pain is sheerly aversive; and that those who inflict pain do so unawares. I argue that these pieties avoid disturbing questions regarding the pain-filled body. The controlled experience of pain is central to any number of practices; many of them place the body in extremis. Conversely, there are practices of pain-infliction undertaken with the expectation of gratification or social validation. Pain, in short, is alluring as well as aversive.